2017
DOI: 10.4317/medoral.21626
|View full text |Cite
|
Sign up to set email alerts
|

Salivary MMP-9 in the detection of oral squamous cell carcinoma

Abstract: BackgroundOral squamous cell carcinoma (OSCC) is the most common malignant tumour of the oral cavity. Detection of OSCC is currently based on clinical oral examination combined with histopathological evaluation of a biopsy sample. Direct contact between saliva and the oral cancer makes measurement of salivary metalloproteinase- 9 (MMP-9) an attractive alternative.Material and MethodsIn total, 30 OSCC patients and 30 healthy controls were included in this prospective study. Saliva samples from both groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 24 publications
2
55
0
1
Order By: Relevance
“…The knockdown of MMP-9 may effectively inhibit OSCC cell metastasis and invasion in xenografted zebrafish. These evidences confirmed that the role of MMP-9 in OSCC cells is consistent with that in series of cancers and relevant clinical researches [15][16][17][18]. As previously described, angiogenesis is an important step of cancer metastasis and facilitates distant metastasis.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The knockdown of MMP-9 may effectively inhibit OSCC cell metastasis and invasion in xenografted zebrafish. These evidences confirmed that the role of MMP-9 in OSCC cells is consistent with that in series of cancers and relevant clinical researches [15][16][17][18]. As previously described, angiogenesis is an important step of cancer metastasis and facilitates distant metastasis.…”
supporting
confidence: 90%
“…The overexpression of MMP-9 in human OSCC tissues may contribute to cancer metastasis, suggesting that MMP-9 may serve as a prognostic biomarker of OSCC [15,16]. In addition, the elevated MMP-9 level in saliva may be a useful diagnostic factor for the early detection of OSCC [17,18]. Although the high expression of MMP-9 was considered to be associated with the invasion of OSCCs in clinical studies, further basic studies in vivo and in vitro are necessary to confirm the role of MMP-9 in OSCCs and provide scientific validation.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies evaluated various tumor markers in the saliva of OSCC subjects (Ghallab and Shaker, 2017;Peisker et al, 2017;Lee et al, 2018). There is a need to identify specific and sensitive molecular biomarkers, which can be used to screen OSCC and OPMD.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco, if consumed in various forms, causes surface changes and keratinization in mucosa which leads to alteration of MMP-9 secretion. This change in concentration can be traced in serum as well as the saliva of cancer subjects and subjects diagnosed with OPMD (Peisker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinase‐B (MMP‐9) is another promising salivary protease marker with reported single SE and SP of 100% and 26.7%‐79%, respectively . A recent meta‐analysis of 9 diagnostic salivary biomarker studies concluded that MMP‐9 and chemerin together possessed excellent diagnostic validity and constituted the most sensitive and specific OSCC panel yet …”
Section: Proteomic/peptidomic Biomarker Combinationsmentioning
confidence: 99%